2012
DOI: 10.1097/pas.0b013e31825fa4b4
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphologic and Molecular Features of Pouch and Peripouch Adenocarcinoma

Abstract: The occurrence of adenocarcinoma after ileal pouch-anal anastomosis for ulcerative colitis (UC) is an infrequent but potentially lethal complication. Neither histomorphologic nor molecular features of pouch adenocarcinoma after ileal pouch-anal anastomosis have been fully investigated. We report the largest series of 12 pouch and peripouch adenocarcinomas and compared them with 58 randomly selected UC-associated adenocarcinomas. The mean age of patients with pouch/peripouch adenocarcinoma was 55.2 years (SD 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…CK7 immunoreactivity has been routinely used in pathology practice to determine the possible origin of metastatic adenocarcinoma. It has been recently described in small bowel adenocarcinoma, 16 pouch and peri-pouch adenocarcinoma, 5 and inflammatory bowel disease-associated neoplasia in small series. [6][7][8] However, CK7 immunoreactivity in inflammatory bowel disease-associated neoplasia has not been well investigated in a cohort with reasonable size.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…CK7 immunoreactivity has been routinely used in pathology practice to determine the possible origin of metastatic adenocarcinoma. It has been recently described in small bowel adenocarcinoma, 16 pouch and peri-pouch adenocarcinoma, 5 and inflammatory bowel disease-associated neoplasia in small series. [6][7][8] However, CK7 immunoreactivity in inflammatory bowel disease-associated neoplasia has not been well investigated in a cohort with reasonable size.…”
Section: Discussionmentioning
confidence: 97%
“…3 This was demonstrated by the distinct histomorphology of colitis-associated colorectal adenocarcinoma. 4 In addition, our previous study on ileal pouch and peri-pouch adenocarcinomas developed in inflammatory bowel disease patients showed that approximately 60% of these tumors expressed CK7, rarely had nuclear b-catenin accumulation, 5 in contrast to the pattern seen in sporadic colorectal adenocarcinoma. 6 Therefore, CK7 expression may be associated with tumorigenesis in inflammatory bowel disease.…”
mentioning
confidence: 99%
“…21,22 Aberrant expression of miRNA-31 has been briefly mentioned in inflammatory bowel disease patients in a prior study of inflammatory bowel disease-associated colon cancer, but it has not been recognized as a specific marker in inflammatory bowel disease. 13 In this study, we emphasize the role of miR-31 as a universal biomarker of idiopathic inflammatory bowel 23 while the non-inflammatory bowel disease patients are largely free of the risk and are spared from difficult and costly cancer surveillance. This study brings several advances, as (1) the first report assessing miR-31 expression in inflammatory bowel disease in formalin-fixed, paraffin-embedded tissue; (2) the first report to identify aberrant expression of miR-31 in inflammatory bowel disease independent of inflammatory activity; and (3) an addition to small but growing knowledge of miRNA analysis by next-generation sequencing in colonic mucosa of inflammatory bowel disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…Only a limited number of cases of adenocarcinoma in an intestinal pouch have been described so far [24][25][26], while dysplasia of different degrees can be seen in 4.4% of intestinal pouches [6]. In the present study no cases of dysplasia were diagnosed.…”
Section: Discussionmentioning
confidence: 41%
“…Some authors suggest that a malignancy developing in an intestinal pouch may in fact be cancer of ileal-anal anastomosis originating from the remaining "cuff" of rectal mucosa [28,29]. Jiang et al describe the features of 12 cases of pouch and peripouch adenocarcinoma, and there was just 1 in the pouch only; 8 in the anal transitional zone (ATZ, defined as the part of the rectum between the dentate line and anastomosis); 2 in the ATZ and pouch; and 1 in a nonspecific peripouch region [26] In the present study, in addition to the clinical, endoscopic and histological evaluation of intestinal pouches, a microbiological assessment of material collected from pouch lumen was performed. The main components of the bacterial flora of the intestinal pouches were aerobic species.…”
Section: Discussionmentioning
confidence: 99%